2018
DOI: 10.1051/e3sconf/20182801025
|View full text |Cite
|
Sign up to set email alerts
|

Regions of pollution with particulate matter in Poland

Abstract: Abstract. The study presents the temporal and spatial variability of particulate matter concentration in Poland in the calendar winter season (December-February). The basis for the study were the hourly and daily values of particulate matter PM10 concentration from the period 2005/06 -2014/15, obtained from 33 air pollution monitoring stations. In Poland, the obligation to monitor the concentration of the finer fraction of particles smaller than 2.5μm in aerodynamic diameter was introduced only in 2010. Conseq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…The cases of hourly concentrations over 100 μg•m −3 occurred in Sopot and Gdynia with a frequency of no more than 1.8% and, in Gdańsk, approximately twice more often. The distribution of the hourly PM10 concentration presented above is characteristic for the whole region of northern Poland, as was shown by Rawicki et al [50].…”
Section: General Description Of Pm 10 and Meteorology Variablessupporting
confidence: 72%
“…The cases of hourly concentrations over 100 μg•m −3 occurred in Sopot and Gdynia with a frequency of no more than 1.8% and, in Gdańsk, approximately twice more often. The distribution of the hourly PM10 concentration presented above is characteristic for the whole region of northern Poland, as was shown by Rawicki et al [50].…”
Section: General Description Of Pm 10 and Meteorology Variablessupporting
confidence: 72%
“…The division of Poland according to the frequency of smog episodes is shown in Figure 2. In 2018, Rawicki et al [19] showed that due to meteorological conditions and the occurrence of smog episodes, Poland could be divided into three areas: I-southern, in which smog episodes last the longest and occur most often, II-central with moderate frequency of smog episodes and III-northern, where smog episodes occur sporadically. This is due to the fact that a constant balance dominates in the southern part of Poland, and a much larger share of unstable balance occurs in the northern part [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…The very high share of particulate matter fraction < 2.5 µg in pollution with particulate matter is evidenced by the results from a series of previous winter seasons (2009/10-2014/15) recorded all over the country. In some regions of Poland, the hourly particulate matter concentrations, which generally fell between 0 and 75 µg•m −3 , were recorded more frequently with respect to PM 2.5 than PM 10 , in a longer, i.e., 10 year-long, series of winter seasons (2005/06-2014/15) [34].…”
Section: Particulate Matter Concentrationsmentioning
confidence: 97%